ANALISIS PELAKSANAAN STANDAR PELAYANAN MINIMAL (SPM) RUMAH SAKIT DI INSTALASI FARMASI RUMAH SAKIT BHAYANGKARA MANADO - Puspitasari, Putri Angelina; Lolo, Widya Astuty; Rundengan, Gerald (UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACTImplementation of Hospital Minimum Serviced Standard is very important because it is a measured of the performanced of health serviced held in hospitals. This studied aims to determined the suitability of the MSS of pharmacy hospitals on the indicator of the length of time of prescription serviced and the indicators of patient satisfaction at the Bhayangkara Hospital, Manado. This researched used a descriptive type of researched conducted with quantitative and qualitative researched methoded. The sampled for this studied was 343 path patients or prescriptions IFRS Bhayangkara Manado. The results showed that the indicator for the length of time of prescription serviced obtained the averaged time for non-concocted prescriptions for 9.30 minuted and 22 minuted for prescription concocted, and for indicators of patient satisfaction, the result was 80.63%. Based on the results of the researched obtained, it can be concluded that the Bhayangkara Manado Hospital has met the standards according to the Decree of the Minister of Health of the Republic Indonesia Number 129 / MENKES / SK / II / 2008 concerning Minimum Serviced Standards for Hospitals in the Pharmacy Sector that have been set by the Ministry of Health of the Republic Indonesia. Keywords: MSS, Waiting Time, Patient Satisfaction, IFRS ABSTRAKImplementasi Standar Pelayanan Minimal Rumah Sakit sangat penting karena merupakan tolak ukur kinerja pelayanan kesehatan yang diselenggarakan di rumah sakit. Penelitian ini betujuan untuk mengetahui kesesuaian SPM rumah sakit bidang farmasi pada indikator lama waktu pelayanan resep dan pada indikator kepuasan pasien di Rumah Sakit Bhayangkara Manado. Penelitian ini menggunakan jenis penelitian deskriptif yang dilakukan dengan metode penelitian kuantitatif dan kualitatif. Sampel untuk penelitian ini sebanyak 343 pasien/resep di IFRS Bhayangkara Manado. Hasil penelitian menunjukkan bahwa pada indikator lama waktu pelayanan resep diperoleh waktu rata – rata untuk resep non racikan selama 9,30 menit dan resep racikan selana 22 menit, serta untuk indikator kepuasan pasien diperoleh hasil sebesar 80,63%. Berdasarkan hasil penelitian yang diperoleh, maka dapat disimpulkan bahwa Rumah Sakit Bhayangkara Manado telah memenuhi standar menurut Keputusan Menteri Kesehatan Republik Indonesia Nomor 129/MENKES/SK/II/2008 tentang Standar Pelayanan Minimal Rumah Sakit Bidang Farmasi yang telah ditetapkan oleh Departemen Kesehatan Republik Indonesia Kata kunci: SPM, Waktu Tunggu, Kepuasan Pasien, IFRS